Electron acceptors for anaerobic oxidation of methane drive microbial community structure and diversity in mud volcanoes. (3rd May 2018) - Ren, Ge; Ma, Anzhou; Zhang, Yanfen; Deng, Ye; Zheng, Guodong; Zhuang, Xuliang; Zhuang, Guoqiang; Fortin, Danielle
Summary: Mud volcanoes (MVs) emit globally significant quantities of methane into the atmosphere, however, methane cycling in such environments is not yet fully understood, as the roles of microbes and their associated biogeochemical processes have been largely overlooked. Here, we used data from high‐throughput sequencing of microbial 16S rRNA gene amplicons from six MVs in the Junggar Basin in northwest China to quantify patterns of diversity and characterize the community structure of archaea and bacteria. We found anaerobic methanotrophs and diverse sulfate‐ and iron‐reducing microbes in all of the samples, and the diversity of both archaeal and bacterial communities was strongly linked to the concentrations of sulfate, iron and nitrate, which could act as electron acceptors in anaerobic oxidation of methane (AOM). The impacts of sulfate/iron/nitrate on AOM in the MVs were verified by microcosm experiments. Further, two representative MVs were selected to explore the microbial interactions based on phylogenetic molecular ecological networks. The sites showed distinct network structures, key species and microbial interactions, with more complex and numerous linkages between methane‐cycling microbes and their partners being observed in the iron/sulfate‐rich MV. These findings suggest that electron acceptors are important factors driving the structure of microbial communities in these methane‐rich environments.